Os recursos hídricos do Rio Grande do Norte: uma análise da vulnerabilidade territorial ao colapso no abastecimento de água - Adriano Lima Trolei; Bruno Lopes da Silva (Confins)
This article proposes a discussion in how the structure of hydric resources represented by its existing natural and technical elements has characterized the process of human supply facing the drought experienced in the last years and the consequent vulnerability of hydric collapse in the scope of Rio Grande do Norte. From this scenario, and from a set of natural and technical elements present in every municipality, hydric potentialities and fragilities were identified of the following variables: precipitation, hydrographic basin, aquifer system, pipelines network, reservoir levels, use of water tank trucks and supply situation. The conceptual theoretical contribution was built from three thematic axes: the structure of hydric resources, the potentialities and fragilities, and the vulnerability to hydric collapse. The construction of the empirical part occurred through elaboration of a database from 2015 to 2017 about the natural and technical elements of Rio Grande do Norte hydric resources. This data was obtained along the following public agencies: Instituto de Desenvolvimento Sustentável e Meio Ambiente – IDEMA, Agência Nacional de Águas - ANA, Secretaria de Meio Ambiente e dos Recursos Hídricos do Rio Grande do Norte – SEMARH, Departamento Nacional de Obras Contra a Seca- DNOCS e Companhia de Águas e Esgotos do Rio Grande do Norte – CAERN. Having the objective to estimate the vulnerability to hydric collapse in every Rio Grande do Norte municipality the methodology proposed by Crepani, Medeiros, Hernandez Filho et al (2001) was used, which integrates variables and categories of vulnerability and classifies them from Basic Territorials Units (Unidades Territoriais Básicas – UTB) into three levels: Units of low, medium and high vulnerability to hydric collapse. The result of the integrated analysis of the variables characterized Rio Grande do Norte with only two levels: one level with 20 municipalities which presented medium vulnerability to hydric collapse located in the East coast and in the center north region of the state and the other level composed of 147 municipalities with high vulnerability to hydric collapse. This result shows that Rio Grande do Norte has a high criticality to hydric collapse. In this context it is suggested that managers think the territory as an integrated and systemic way, considering the interrelation of natural and technical elements in each system of water supply.